2023
DOI: 10.3389/fpls.2023.1151786
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of cerium oxide nanoparticles alone and in combination with cadmium on nutrient acquisition and the growth of maize (Zea mays)

Abstract: IntroductionThe increasing use of cerium nanoparticles (CeO2-NPs) has made their influx in agroecosystems imminent through air and soil deposition or untreated wastewater irrigation. Another major pollutant associated with anthropogenic activities is Cd, which has adverse effects on plants, animals, and humans. The major source of the influx of Cd and Ce metals in the human food chain is contaminated food, making it an alarming issue; thus, there is a need to understand the factors that can reduce the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Interestingly, we observed that the NP-treated root systems formed significantly fewer root forks compared to the control, which clearly indicated the specific architecture of chrysanthemum roots forming in the presence of NPs. Similarly, in Zea mays L., the application of cerium oxide nanoparticles resulted in a decrease in the number of root forks (Ayub et al, 2023).…”
Section: Contrastsmentioning
confidence: 96%
“…Interestingly, we observed that the NP-treated root systems formed significantly fewer root forks compared to the control, which clearly indicated the specific architecture of chrysanthemum roots forming in the presence of NPs. Similarly, in Zea mays L., the application of cerium oxide nanoparticles resulted in a decrease in the number of root forks (Ayub et al, 2023).…”
Section: Contrastsmentioning
confidence: 96%